'Unpleasant and undreamt of experiences of human nature': a Refocus on Thorp Green. (2nd July 2020) - Chitham, Edward
Abstract : In this article I re-examine the milieu at Thorp Green during, before and after Anne Brontë's stay there. Though Branwell is not the chief focus, slight doubt is cast on his account of events. There may be other explanations of some of what he reports. Use will be made of research by Bob Gamble, with many thanks.